2006
DOI: 10.1080/14330237.2006.10820129
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Awareness of In—School Adolescents in Nigeria: Implications for Adolescence Sexuality

Abstract: This study investigated HIV/AIDS awareness of in-school adolescents in Nigeria to determine their risk for contracting HIV/AIDS. A total of 892 purposively selected adolescents (mean age = 16. 5 years; SD = 5. 2; males = 492; females = 400) participated in the study. The participants responded to the HIV/AIDS Awareness Inventory (HAAI). The questions on the survey included the following aspects: meaning of HIV/AIDS; prevalence; mode of transmission; consequences and prevention. Differences in gender, age, scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…This could be due to the fact that HIV/AIDS enlightening programs, through the mass and electronics media are more prominent in urban areas than in rural areas. This finding is related to an earlier study by Esere (2006) which indicated that HIV/AIDS awareness is lower among rural teenagers than their urban colleagues. However, the study by Ugwuegbulem (2001) indicated that geographical location had no significant in-…”
Section: Discussionsupporting
confidence: 85%
“…This could be due to the fact that HIV/AIDS enlightening programs, through the mass and electronics media are more prominent in urban areas than in rural areas. This finding is related to an earlier study by Esere (2006) which indicated that HIV/AIDS awareness is lower among rural teenagers than their urban colleagues. However, the study by Ugwuegbulem (2001) indicated that geographical location had no significant in-…”
Section: Discussionsupporting
confidence: 85%
“…It was assumed that such information might encourage promiscuity among adolescents rather than helping them to reduce the consequences of unprotected sex. Matters relating to sex and sexuality are usually shrouded with secrecy, so that adolescent youths find it difficult to access needed information in this regard (Esere 2006(Esere , 2008. Similarly, in the Nigerian context, the head of a household is often a male adult irrespective of whether he is the bread-winner or not.…”
Section: Discussion Of Results and Conclusionmentioning
confidence: 99%
“…Despite increased sexual knowledge, adolescents in Nigeria are poor contraceptive users [14]. They are less likely than adults to consistently use condoms or other modern methods of contraceptives that could reduce their chances of infection [4].…”
Section: Introductionmentioning
confidence: 99%